2015
DOI: 10.1021/acs.energyfuels.5b01909
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Fe–Zn–Cu Sorbents Supported on Activated Lignite Char for the Desulfurization of Coke Oven Gas

Abstract: In this paper, the regeneration characteristics of activated-char-supported Fe–Zn–Cu sorbents were studied. The desulfurization and regeneration experiments were carried out using a quartz fixed-bed reactor at ambient pressure. The effects of regeneration conditions, such as space velocity, temperature, and steam concentration, on the regeneration performance were examined. The crystal phase, chemical structure of activated components, and physical structure of sorbents before and after regeneration were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Usually, the conditions of char's production are adjusted in order to obtain materials with suitable properties [27]. Special modifications using chemicals, such as caustic impregnations or activation [28][29][30] and metal impregnation [21,22,[31][32][33][34] are carried out to enhance the activated carbon efficiency. However, these processes have high environmental footprint (use and management of chemicals), increase the cost of the materials and jeopardize their regeneration (low temperature of self-ignition) [35].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the conditions of char's production are adjusted in order to obtain materials with suitable properties [27]. Special modifications using chemicals, such as caustic impregnations or activation [28][29][30] and metal impregnation [21,22,[31][32][33][34] are carried out to enhance the activated carbon efficiency. However, these processes have high environmental footprint (use and management of chemicals), increase the cost of the materials and jeopardize their regeneration (low temperature of self-ignition) [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have reported H 2 S removal in COG by iron-based adsorbents, such as iron oxide and/or iron-bearing sorbents combined with other metals. [24][25][26][27] It is well-known that a typical COG is composed of 54-59% H 2 , 24-28% CH 4 , 4-7% CO, 3-5% CO 2 , 1-3% CO 2 and 1-3% H 2 O with impurities, but the influence of the individual COG components on H 2 S removal has not been investigated in previous reports. [24][25][26][27] In this paper, therefore, we focus on investigating H 2 S removal and catalytic NH 3 decomposition performance using an Australian limonite in the presence of COG components to develop a novel gas cleaning method for removing H 2 S and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the developed pore structure is also a typical character of chars derived from LRC pyrolysis. With further activation methods, chars can be served as adsorbing materials or catalyst supports [19][20][21]. Gas products, derived from LRC pyrolysis, are full of H 2 , CO and CH 4 , which are able to be fuels or chemical synthesis after purification.…”
Section: Pyrolysis Of Low-rank Coal and Its Products 21 Pyrolysis Omentioning
confidence: 99%